2017
DOI: 10.4103/ijo.ijo_938_16
|View full text |Cite
|
Sign up to set email alerts
|

Late dislocation of in-the-bag intraocular lenses in uveitic eyes: An analysis of management and complications

Abstract: Aim:An analysis of late in-the-bag dislocation of intraocular lenses (IOL), in uveitic eyes.Setting:Referral uveitis clinic.Design:Retrospective case series.Materials and Methods:All case records of eyes with chronic uveitis that had phacoemulsification with IOL implantation, at a referral uveitis clinic between February 1997 and January 2015 were retrieved and analyzed. Only those eyes with no documented intraoperative complication and no predisposing risks to IOL dislocation, such as pseudoexfoliation, high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Pooled analysis showed that the two procedures had a similar effect on BCVA (MD -0.00, 95%CI: -0.08 to 0.08, P = 0.99; Fig 2A ). We obtained similar results after excluding one small study [10] ( Fig 2B ). Pooled analysis of the two studies reporting the change in BCVA as a result of surgery showed the two procedures to be similar (MD 0.09, 95%CI -0.08 to 0.26, P = 0.32; Fig 2C ).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Pooled analysis showed that the two procedures had a similar effect on BCVA (MD -0.00, 95%CI: -0.08 to 0.08, P = 0.99; Fig 2A ). We obtained similar results after excluding one small study [10] ( Fig 2B ). Pooled analysis of the two studies reporting the change in BCVA as a result of surgery showed the two procedures to be similar (MD 0.09, 95%CI -0.08 to 0.26, P = 0.32; Fig 2C ).…”
Section: Resultssupporting
confidence: 80%
“…This alters the position of the IOL-bag complex, ultimately dislocating it [12,32,33]. Other risk factors for IOL dislocation included trauma [7,9,11,14,18,21], high myopia [11,14,24], previous intraocular surgery [14,1820], capsulotomy or capsular rupture [7,11,1820,23], uveitis [9,10,14], Marfan’s syndrome [24], retinitis pigmentosa [5].…”
Section: Discussionmentioning
confidence: 99%
“…In relatively large studies, 6 of 1056 patients with uveitis (0.57%) 4 and 11 of 581 patients (1.89%) 5 that underwent cataract surgery were reported to have a late dislocation of the IOL. Fuchs’ heterochronic uveitis, multifocal choroiditis, birdshot retinochoroiditis, chronic intermediate, chronic idiopathic pan uveitis, and sympathetic ophthalmitis were diagnosed in 6 of the 1056 patients who had an IOL dislocation.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 In uveitis patients who had undergone cataract surgery, a late in-the-bag IOL dislocation was found in only 6 of 1056 (0.57%) eyes in one study 4 and 10 of 581 (1.89%) eyes in another study. 5 The majority of these eyes had intermediate uveitis. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…[27] Late dislocation of capsular bag IOL has been reported in uveitic eyes. [2829] Since uveitic eyes are more prone for zonular dehiscence on long term, there can be decenteration or tilt induced by zonular weakness. Transscleral fixated IOL has shown better outcomes compared to sutured scleral fixated IOL as studied by Sinha et al [30] Todorich et al reported 5 eyes with uveitis showing good visual outcomes after intrascleral IOL fixation.…”
Section: Discussionmentioning
confidence: 99%